Kanonisasi Jonathan Brown Atas Shahih Al-Bukhari - Hasan, Mochamad Ismail (Living Islam: Journal of Islamic Discourses, 2019)
Shahih Bukhari is one of hadith collections endowed a high authority by consensus for muslim. The consensus is not simply acknowledged by hadis scholars, but by also scholars in varied legal schools. In additions to its standard of hadith authenticity become a convention measure to evaluate other hadith that there is not in Shahih Bukhari. It is Jonathan Brown that has researched how process of canonization of Shahih Bukhari collection. In his research, Brown showed that Shahih Bukhari canon (convention measure of hadith authenticity) was established by long process time. Part of its processes is efforts to study critically the collection to discover its measure of hadith authenticity that al-Bukhari, as the author employed it and then to apply the measure to the hadith else. In the other hand, the notion of consensus (ijma’) used in legal scholars discourse of varied schools also played the impor- tant role to result authority of the collection. The authority of the collection also was supported by scholars declara- tion continously from generation to generation. Some of them are Abu Ishaq al-Isfarayani, Abu Nashr al-Wa’iliy and al-Juwaini.